QCD at nonzero chemical potential and temperature from the lattice - Chris Allton (2002)
A study of QCD at non-zero chemical potential, mu, and temperature, T, is performed using the lattice technique. The transition temperature (between the confined and deconfined phases) is determined as a function of mu and is found to be in agreement with other work. In addition the variation of the pressure and energy density with mu is obtained for small positive mu. These results are of particular relevance for heavy-ion collision experiments.